A method for improving the drying and redispersion efficiency of nanofibers
By combining drying and dehydrating and hydrating treatment, the nanofiber network structure is coordinated and the mechanical effect is assisted, the problem of low redispersion efficiency after nanofiber drying is solved, and efficient redispersion and stable nanofiber dispersion liquid is achieved, which is suitable for composite materials and other fields.
Patent Information
- Application Number
- CN202210936370.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-08-05
AI Technical Summary
Nanocellulose and nanochitin form irreversible hydrogen bonds during drying, resulting in low redispersion efficiency after drying, and the dispersion effect before drying is not achieved, which seriously hinders subsequent application research.
By combining drying and dehydration with water and moistening, the relationship between drying time and nanofiber network structure is coordinated to ensure that water molecules are fully immersed in the fiber network, expand the void structure of the fiber network, and assist in slight mechanical action to obtain a stable nanocellulose/nanochitin dispersion liquid with high redispersion efficiency. Further, by adding sodium lignin sulfonate, hydrogen bond formation is hindered and the redispersion efficiency is improved.
It realizes efficient redispersion after nanofiber drying, with a redispersion efficiency of up to 50-95%, and maintains the transmittance and mechanical properties of the nanofiber dispersion before the original drying.
Smart Images

Figure CN115160594B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nanofiber drying and redispersion, and in particular relates to a method for improving the redispersion efficiency of nanofibers after drying. Background Art
[0002] Nanocellulose and nanochitin have attracted great attention as biodegradable and renewable nanomaterials with excellent properties such as high modulus, low thermal expansion coefficient and high mechanical strength. However, nanocellulose and nanochitin form irreversible hydrogen bonds during the drying process, and the hydrogen bonds cannot be completely broken during redispersion, which easily leads to flocculation and aggregation. The redispersion efficiency is low, and the dispersion effect before drying cannot be achieved, which seriously hinders subsequent application research.
[0003] The morphology, steric hindrance, surface charge, interfacial compatibility and dispersion medium of nanocellulose are all important factors affecting the formation of hydrogen bonds between cellulose molecules. Patent CN114058027A proposes that by adding lignin sulfonate, micro-nanocellulose can be redispersed to obtain a stable suspension. However, nanocellulose is smaller than micro-nanocellulose, and the specific surface area of nanocellulose is an order of magnitude multiple of micro-nanocellulose. Therefore, the entanglement between its fibers and the resulting hydrogen bonding are stronger, while the hydrogen bonding between micro-nano fibers is obviously relatively weak. Therefore, the method of adding lignin sulfonate alone is not suitable for the redispersion of nanocellulose. At present, the aggregation of nanocellulose after drying is improved mainly from three aspects. The first is the drying method, such as controlling the solid content before drying (above 4%) and changing the solvent during drying (ethanol, ethylene glycol, tert-butanol, etc.), but the experimental steps are cumbersome and cannot be implemented on a large scale; the second is to add a capping agent to the suspension to reduce the formation of hydrogen bonds, but the subsequent treatment steps for removing the capping agent are cumbersome, which affects the application performance; the third is to improve the hydrophilicity of nanocellulose through grafting modification methods such as esterification, acetylation, and silanization, so that it can be better dispersed in the aqueous phase, but there are defects such as harsh operating conditions and limited modification efficiency.
[0004] The present invention is proposed in view of the above. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a simple and efficient method for improving the redispersion efficiency of nanofibers after drying, which is mainly achieved by combining drying and dehydration with water swelling, coordinating the relationship between drying time and nanofiber network structure, ensuring that water molecules are fully immersed in the fiber network, expanding the void structure of the fiber network, and then obtaining a stable nanocellulose / nanochitin dispersion with high redispersion efficiency under the assistance of slight mechanical action; further, sodium lignin sulfonate can be added to the nanofiber dispersion to hinder the formation of hydrogen bonds during nanofiber drying and dehydration, thereby further improving the redispersion efficiency, obtaining a stable nanofiber dispersion containing lignin functional factors, and also having the function of improving the suspension stability of the fracturing fluid.
[0006] Technical solution: The present invention provides a method for improving the redispersion efficiency of nanofibers after drying, comprising the following steps:
[0007] (1) drying the nanocellulose / nanochitin dispersion to make the water content of the nanocellulose / nanochitin less than 5%;
[0008] (2) Then it is treated with water to swell for 0.5h-12h;
[0009] (3) Finally, a stable nanocellulose / nanochitin dispersion with high redispersion efficiency is obtained through redispersion treatment.
[0010] Furthermore, in step (1), the nanocellulose / nanochitin dispersion is prepared by any one of chemical pretreatment combined with mechanical treatment, enzyme pretreatment combined with mechanical treatment, and mechanical treatment;
[0011] Furthermore, the concentration of the nanocellulose / nano-chitin dispersion is 0.1-5%; the concentration of the redispersed nanocellulose / nano-chitin dispersion is 0.1-5%; and the redispersion efficiency is 50%-80%.
[0012] Furthermore, in the step (1), the nanocellulose / nanochitin dispersion is dried in an atmospheric pressure oven or vacuum dried to obtain a nanofiber film, and the drying temperature is 20 to 80°C.
[0013] Furthermore, in the step (1), the nanocellulose / nanochitin dispersion is freeze-dried to obtain nanofiber aerogel or spray-dried to obtain nanofiber particles.
[0014] Furthermore, the redispersion treatment in step (3) adopts at least one of an ultrasonic crusher, an ultrafine particle crusher, and a high-pressure homogenizer; preferably, the treatment time is 1 to 5 minutes.
[0015] Furthermore, the processing power of the ultrasonic crusher is 150-500W.
[0016] Furthermore, in step (1), sodium lignin sulfonate is added to the nanocellulose / nanochitin dispersion.
[0017] Furthermore, the concentration of the sodium lignin sulfonate in the dispersion is 0.001-1.5%, and the sodium lignin sulfonate accounts for 1-30% of the absolute dry mass of the nanocellulose; preferably, the redispersion efficiency is 60%-95%.
[0018] A redispersible nanofiber dispersion is prepared by the method for improving the drying and redispersing efficiency of nanocellulose; preferably, the size range of the redispersible nanofiber is 2-40nm in width and 100-3000nm in length, and the redispersible liquid permeability is 50-95%.
[0019] The invention discloses an application of a nanofiber dispersion liquid, and the application of the redispersed nanofiber dispersion liquid in the fields of composite materials, plastics, rubber, fracturing fluid, water reducing agent, etc.
[0020] Beneficial effects:
[0021] (1) The method proposed in the present invention can effectively improve the redispersion efficiency of the nanofibers after drying, and the redispersion efficiency is as high as 50-95%.
[0022] (2) The redispersed nanofiber dispersion obtained by the present invention can maintain the same transmittance as the original nanofiber dispersion before drying; the crystal structure and microscopic morphology of the redispersed nanofibers are consistent with those of the nanofibers before drying; the mechanical properties and thermodynamic properties of the nanofiber film after redispersion are also consistent with those before drying.
[0023] (3) The present invention uses a coordinated treatment of dehydration and water swelling to weaken the hydrogen bonding between nanofibers formed during the dehydration process, thereby achieving efficient redispersion. The method of the invention does not involve complex drying condition adjustment, end-capping agent removal, and chemical modification, and has the advantages of being simple, energy-saving, efficient, and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 Optical photos of nanocellulose under polarized light after mechanical treatment after different water swelling times under freeze drying and atmospheric pressure drying conditions;
[0026] Figure 2 The redispersion rate of nanocellulose after different drying methods and different water swelling times;
[0027] Figure 3 The pore changes of nanocellulose film after different swelling time;
[0028] Figure 4 The effect of different addition amounts of sodium lignin sulfonate on the redispersion rate of nanocellulose;
[0029] Figure 5 The redispersion rate of different raw materials under the conditions of water swelling treatment and adding sodium lignin sulfonate treatment;
[0030] Figure 6 The viscosity change of nanocellulose suspension before and after redispersion;
[0031] Figure 7 TEM images of the suspension before and after redispersion;
[0032] Figure 8 The changes of mechanical properties of nanocellulose films before and after redispersion;
[0033] Fig. 9 After adding sodium lignin sulfonate, the film has UV shielding properties;
[0034] Fig.10 The invention relates to the application of redispersible fluid in the field of fracturing fluid. DETAILED DESCRIPTION
[0035] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but those skilled in the art will appreciate that the following embodiments and examples are only used to illustrate the present invention and should not be considered as the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. If no specific conditions are specified, they are carried out according to conventional conditions or conditions recommended by the manufacturer.
[0036] Embodiment 1:
[0037] The nanocellulose used in the present invention is prepared from raw material bleached hardwood kraft pulp HBKP through TEMPO / NaBr / NaClO chemical oxidation method and synergistic effect of high-pressure homogenization to obtain nanocellulose TOCN; nanochitin is prepared from chitin raw material through TEMPO / NaBr / NaClO chemical oxidation method to obtain TOChN; CNC is spray-dried cellulose nanocrystal powder purchased from Shansi Technology; MNC is micro-nano cellulose prepared by ultrafine particle grinding and pure mechanical treatment.
[0038] Among them, the nanofibers involved in the present invention are not limited to the above-mentioned methods. Nanocellulose prepared by biological oxidation method (such as enzyme oxidation), chemical oxidation method (such as TEMPO / NaBr / NaClO oxidation, TEMPO / laccase / O2 oxidation) and / or mechanical treatment method (high-pressure homogenization treatment, ultrasonic crushing treatment, ultrafine grinding treatment, colloid milling treatment, microjet treatment) are all within the scope of the present invention.
[0039] The amount of the nanocellulose / nanochitin dispersion provided by the present invention can be flexibly adjusted according to factors such as the actual use environment, mold size, and test requirements. The following examples illustrate the present invention by taking 0.1 g of absolutely dry nanofibers as an example.
[0040] Embodiment 2:
[0041] Take 0.1g of TOCN nanofibers with an absolute dry mass of 0.2% and pour them into a plastic culture dish, dry them at 40°C, and swell the obtained nanocellulose film with a water content of 1% in water for 2 hours, redisperse it at a concentration of 0.2%, and treat it with an ultrasonic mechanical device with a power of 500w for 1 minute. After centrifugation, a stable nanocellulose dispersion is obtained, and the redispersibility is 58% after concentration testing. This shows that the nanocellulose film can achieve a high redispersibility after a simple water swelling effect.
[0042] The raw material used for the nanocellulose suspension of the present invention is not limited to TOCN. The effect of raw material changes on the redispersion efficiency is investigated, as shown in Table 1.
[0043] Table 1
[0044]
[0045] Embodiment 3:
[0046] Take 0.1g of TOCN nanofibers with an absolute dry mass of 0.2% and pour them into a plastic culture dish, dry them at 50°C, and swell the obtained nanocellulose film with a water content of 1% in water for 4 hours, redisperse it at a concentration of 0.2%, and treat it with an ultrasonic mechanical device with a power of 500w for 1 minute. After centrifugation, a stable nanocellulose dispersion is obtained, and the redispersibility is 71% as determined by the concentration test. This indicates that the redispersibility of nanofibers can be further improved by prolonging the water swelling time.
[0047] The water swelling treatment time used in the present invention is not limited to 4 hours. The effect of the water swelling time alone on the redispersion rate is investigated at swelling times of 0.5 to 12 hours, as shown in Table 2.
[0048] Table 2
[0049]
[0050]
[0051] Embodiment 4:
[0052] 0.1 g of absolute dry mass of nanofiber TOCN with a concentration of 0.1% was taken and poured into a plastic culture dish, dried at 40°C, and the obtained nanocellulose film with a water content of 1% was swelled in water for 2 hours, redispersed at a concentration of 0.1%, and subjected to ultrasonic mechanical treatment with a 500W ultrasonic crusher for 1 minute. After centrifugation, a stable nanocellulose dispersion was obtained, and the redispersion rate was 56% as determined by concentration test.
[0053] The concentration of the nanocellulose suspension and the redispersed suspension used in the present invention is not limited to 0.2%. At a concentration of 0.1-1%, respectively, when the drying concentration is higher, under the same absolute dry mass conditions, the drying time is shorter, the overlap between the fibers is not tight, and it is easier to open; when the redispersed concentration is higher, the redispersed liquid system is smaller, the average mechanical action is greater, and it is easier to open the hydrogen bonds between the fibers. The effect of the single factor of concentration on the redispersed efficiency is investigated, as shown in Table 3.
[0054] Table 3
[0055]
[0056] Embodiment 5:
[0057] Take 0.1g of TOCN nanofibers with an absolute dry mass of 0.4% and pour them into a plastic culture dish, dry them at 40°C, and swell the obtained nanocellulose film with a water content of 1% in water for 2 hours, redisperse it at a concentration of 0.3%, and treat it with an ultrasonic mechanical treatment of 500w ultrasonic crusher for 1 minute. After centrifugation, a stable nanocellulose dispersion is obtained, and the redispersibility is 61% after concentration test. This shows that after a simple water swelling effect, the nanofibers can achieve a high redispersibility.
[0058] The drying temperature of the nanocellulose suspension used in the present invention is not limited to 40°C, and the temperature range is 20-80°C. The following Examples 6-7 are described with different drying temperatures. Other conditions are consistent with Example 2;
[0059] Embodiment 6:
[0060] Take 0.1g of the absolute dry mass of nanofiber TOCN with a concentration of 0.4%, pour it into a plastic culture dish, dry it at 20℃, and swell the obtained nanocellulose film with a water content of 2% in water for 2h, redisperse it at a concentration of 0.3%, and treat it with ultrasonic mechanical treatment of an ultrasonic crusher with a power of 500w for 1min to obtain a stable nanocellulose dispersion with a redispersion rate of 50%. It shows that when the drying temperature is reduced, the drying time is prolonged, the overlap between fibers is tight, and the redispersion rate is slightly lower.
[0061] Embodiment 7:
[0062] 0.1 g of absolute dry mass of nanofiber TOCN with a concentration of 0.4% was poured into a plastic culture dish and dried at 80°C. The obtained nanocellulose film with a moisture content of 1% was swelled in water for 4 hours, and redispersed at a concentration of 0.3%. After ultrasonic mechanical treatment with a 500W ultrasonic crusher for 1 min, a stable nanocellulose dispersion was obtained, and the redispersion rate was 50%.
[0063] The drying method of the nanocellulose suspension used in the present invention is not limited to oven drying, and freeze drying is used as an example for explanation in the following Example 8.
[0064] Embodiment 8:
[0065] Take 0.1 g of absolute dry mass of nanofiber TOCN with a concentration of 0.4%, freeze-dry the nanocellulose suspension at -20°C, and the obtained nanocellulose aerogel with a water content of 4% is then swelled in water for 2 hours, redispersed at a concentration of 0.3%, and subjected to ultrasonic mechanical treatment with a 500W ultrasonic crusher for 1 min to obtain a stable nanocellulose dispersion with a redispersion rate of 65%.
[0066] Embodiment 9:
[0067] 0.1 g of TOCN nanofibers with an absolute dry mass of 0.2% were poured into a plastic culture dish and dried at 40°C. The obtained nanocellulose film with a water content of 1% was swelled in water for 2 hours, redispersed at a concentration of 0.2%, and subjected to ultrasonic mechanical treatment with a power of 500w for 2 minutes to obtain a stable nanocellulose dispersion with a redispersion rate of 68%. This shows that simple and mild mechanical treatment can effectively promote the efficient redispersion of nanocellulose.
[0068] The processing power of the ultrasonic crusher used in the present invention is not limited to 500W, the processing time is not limited to 1min, the power range is 150-500W, and the processing time is 1-5min. The effects of different powers and different processing times on the redispersion rate are investigated, as shown in Table 4, and the other conditions are consistent with those in Example 9.
[0069] Table 4
[0070] raw material Swelling time / h Drying temperature / ℃ Ultrasonic power Ultrasound time Redispersion rate / % TOCN 2 50℃ 150W 1min 50 TOCN 2 50℃ 150W 3min 56 TOCN 2 50℃ 400W 2min 62 TOCN 2 50℃ 400W 3min 66 TOCN 2 50℃ 500W 1min 63 TOCN 2 50℃ 500W 5min 80
[0071] Embodiment 10:
[0072] Take 0.1g of nanofiber TOCN with a concentration of 0.2% absolute dry mass, add 0.005g sodium lignin sulfonate, accounting for 5% of the absolute dry mass of TOCN, vortex mix evenly, remove bubbles by ultrasound and pour into a plastic culture dish, dry to constant weight at 40°C, swell the obtained nanocellulose film in water for 2h, redisperse at a concentration of 0.2%, and undergo ultrasonic mechanical treatment with a 500w ultrasonic crusher for 1min to obtain a stable nanocellulose dispersion with a redispersion rate of 88%. This shows that nanocellulose is efficiently redispersed under the synergistic effect of swelling and sodium lignin sulfonate.
[0073] The addition amount of sodium lignin sulfonate used in the present invention is not limited to 5%, and the range is 1-30%. The following Examples 11-12 are illustrated with different addition amounts of sodium lignin sulfonate.
[0074] Embodiment 11:
[0075] Take 0.1g of nanofiber TOCN with an absolute dry mass of 0.2%, add 0.001g of sodium lignin sulfonate, accounting for 1% of the absolute dry mass of TOCN, vortex mix evenly, remove bubbles by ultrasound and pour into a plastic culture dish, dry to constant weight at 40°C, swell the obtained nanocellulose film in water for 2h, redisperse at a concentration of 0.2%, and undergo ultrasonic mechanical treatment with an ultrasonic crusher with a power of 500w for 1min to obtain a stable nanocellulose dispersion with a redispersion rate of 73%. It shows that under the synergistic effect of swelling and sodium lignin sulfonate, nanocellulose is efficiently redispersed, and a small amount of sodium lignin sulfonate can improve the redispersion rate of nanocellulose.
[0076] Embodiment 12:
[0077] Take 0.1g of nanofiber TOCN with a concentration of 0.2% absolute dry mass, add 0.02g sodium lignin sulfonate, accounting for 20% of the absolute dry mass of TOCN, vortex mix evenly, remove bubbles by ultrasound and pour into a plastic culture dish, dry to constant weight at 40°C, swell the obtained nanocellulose film in water for 2h, redisperse at a concentration of 0.2%, and undergo ultrasonic mechanical treatment with a 500w ultrasonic crusher for 1min to obtain a stable nanocellulose dispersion with a redispersion rate of 88%. It shows that under the synergistic effect of swelling and sodium lignin sulfonate, nanocellulose is efficiently redispersed, and the more sodium lignin sulfonate is contained, the higher the redispersion rate is.
[0078] The present invention investigates the effect of sodium lignin sulfonate content on the redispersion efficiency of nanocellulose in the range of 1% to 20% of the absolute dry mass of nanocellulose. The specific results are shown in the attached Figure 4 shown.
[0079] Embodiment 13:
[0080] Take 0.1g of nanofiber TOChN with a concentration of 0.2% absolute dry mass, add 0.005g sodium lignin sulfonate, accounting for 5% of the absolute dry mass of TOChN, vortex mix evenly, remove bubbles by ultrasound and pour into a plastic culture dish, dry at 40°C, and swell the obtained nanocellulose film with a water content of 1% in water for 2h, redisperse at a concentration of 0.2%, and undergo ultrasonic mechanical treatment with a power of 500w for 1min to obtain a stable nanocellulose dispersion with a redispersion rate of 92%. It shows that under the synergistic effect of swelling and sodium lignin sulfonate, nanocellulose is efficiently redispersed.
[0081] Embodiment 14:
[0082] Take 0.1g of nanocrystalline CNC with a concentration of 0.2% absolute dry mass, add 0.005g sodium lignin sulfonate, accounting for 5% of the absolute dry mass of CNC, vortex mix evenly, remove bubbles by ultrasound and pour into a plastic culture dish, dry at 40°C, and swell the obtained nanofiber film with a moisture content of 1% in water for 2h, redisperse at a concentration of 0.2%, and undergo ultrasonic mechanical treatment with a power of 500w for 1min to obtain a stable nanocellulose dispersion with a redispersion rate of 94%. It shows that under the synergistic effect of swelling and sodium lignin sulfonate, nanocellulose is efficiently redispersed.
[0083] Table 5 is a simple enumeration of the differences in the redispersion rate of nanocellulose under different treatment conditions in the experiment of the present invention. Serial No. 1-7 is based on Example 2, and the effects of different drying methods (normal pressure drying and freeze drying) and different water swelling time (0.5-6h) on the redispersion rate are investigated; Serial No. 8-11 is based on Example 5, and the redispersion rate under more temperature conditions after water swelling treatment is further explored; Serial No. 12-18 is based on Example 10, and the effects of different sodium lignin sulfonate additions (1-30%) on the redispersion rate are explored; Serial No. 19-20 is based on Example 4, and the effects of different drying concentrations and redispersion concentrations on the redispersion rate are explored; Serial No. 21-24 is based on Example 10, and the raw materials are changed to CNC and TOChN, and the promoting effect of water swelling and sodium lignin sulfonate on the redispersion of different raw materials is studied.
[0084] Table 5
[0085]
[0086] Comparative Example 1:
[0087] 0.1 g of the absolute dry mass of nanocellulose suspension with a concentration of 0.2% was directly poured into a plastic culture dish and dried at 40°C. The obtained nanocellulose film with a water content of 1% was redispersed at a concentration of 0.2%, and directly subjected to ultrasonic mechanical treatment with a power of 500w for 1 minute. The redispersibility of the nanocellulose dispersion was 14%. This shows that when nanocellulose is directly redispersed without swelling treatment, the strong hydrogen bonds formed are difficult to break and cannot be efficiently redispersed.
[0088] Comparative Example 2:
[0089] Take 0.1g of nanocellulose suspension with a concentration of 0.2% absolute dry mass, add 0.03g of sodium lignin sulfonate, accounting for 30% of the absolute dry mass of TOCN, vortex mix evenly, remove bubbles by ultrasound and pour into a plastic culture dish, dry at 40°C, and the obtained nanocellulose film with a water content of 1% is redispersed at a concentration of 0.2%, and subjected to ultrasonic mechanical treatment with a power of 500w for 1min to obtain a nanocellulose dispersion with a redispersion rate of 30%. It shows that the nanofibers are closely overlapped and strong hydrogen bonds are generated. Only by adding sodium lignin sulfonate without the swelling effect of water, it is impossible to achieve efficient redispersion of nanocellulose.
[0090] Comparative Example 3:
[0091] Take 0.1g of nanocellulose suspension with a concentration of 0.2% absolute dry mass, add 0.005g sodium lignin sulfonate, accounting for 5% of the absolute dry mass of TOCN, vortex mix evenly, remove bubbles by ultrasound and pour into a plastic culture dish, dry at 100°C, and swell the obtained nanocellulose film in water for 4h, redisperse at a concentration of 0.2%, and undergo ultrasonic mechanical treatment with a 500w ultrasonic crusher for 1min to obtain a stable nanocellulose dispersion with a redispersion rate of 23%. This shows that nanocellulose dried at high temperature quickly aggregates and has a significant keratinization effect. Under the conditions of swelling and adding sodium lignin sulfonate, it is impossible to achieve efficient redispersion under mild treatment conditions.
[0092] Comparative Example 4:
[0093] Take 0.1g of nanocellulose suspension with an absolute dry mass of 0.2%, add 0.1g of sodium lignin sulfonate, accounting for 100% of the absolute dry mass of TOCN, vortex mix evenly, remove bubbles by ultrasound and pour into a plastic culture dish, dry at 40°C, and swell the obtained nanocellulose film in water for 4h, redisperse it at a concentration of 0.2%, and ultrasonically mechanically treat it with an ultrasonic crusher with a power of 500w for 1min to obtain a stable nanocellulose dispersion with a redispersion rate of 89%. It shows that under the synergistic effect of swelling and sodium lignin sulfonate, nanocellulose is efficiently redispersed. However, due to the excessive content of sodium lignin sulfonate, the network structure of the nanocellulose film is destroyed, resulting in a significant decrease in the mechanical properties of the redispersed nanocellulose film, and the tensile strength drops from 110MPa to 45MPa, affecting subsequent applications.
Claims
1. A method for improving the drying and redispersion efficiency of nanofibers, characterized in that: The following steps are involved: (1) firstly subjecting the nanocellulose or nanochitin dispersion to a drying treatment; (2) Then it is treated with water for 0.5h-12h: (3) finally, a redispersion treatment is performed to obtain a stable nanocellulose or nanochitin dispersion having a high redispersion efficiency; the nanocellulose or nanochitin dispersion in the step (1) is dried in an oven at normal pressure or vacuum dried to obtain a nanofiber film, and the drying temperature is 20 to 80° C.; or the nanocellulose or nanochitin dispersion in the step (1) is freeze-dried to obtain a nanofiber aerogel or spray-dried to obtain nanofiber particles.
2. A method for improving the drying and redispersion efficiency of nanofibers according to claim 1, characterized in that: In the step (1), the nanocellulose or nanochitin dispersion is prepared by any one of chemical pretreatment combined with mechanical treatment, enzyme pretreatment combined with mechanical treatment and mechanical treatment; the concentration of the nanocellulose or nanochitin dispersion is 0.1-5%; the concentration of the redispersed nanofiber dispersion is 0.1-5%; and the redispersion efficiency is 50%-80%.
3. A method for improving the drying and redispersion efficiency of nanofibers according to claim 1 or 2, characterized in that: The redispersion treatment in step (3) adopts at least one of an ultrasonic crusher, an ultrafine particle crusher, and a high-pressure homogenizer, and the treatment time is 1 to 5 minutes.
4. A method for improving the drying and redispersion efficiency of nanofibers according to claim 3, characterized in that: The processing power of the ultrasonic crusher is 150-500W.
5. A method for improving drying and redispersion of nanofibers according to claim 1, characterized in that: Add sodium lignin sulfonate to the nanocellulose or nanochitin dispersion in step (1).
6. A method for improving the drying and redispersion of nanofibers according to claim 5, characterized in that: The concentration of the sodium lignin sulfonate in the dispersion is 0.001-1.5%, and the sodium lignin sulfonate accounts for 1-30% of the absolute dry mass of the nanocellulose; and the redispersion efficiency is 60%-95%.
7. A redispersed nanofiber dispersion, characterized in that: The nanofiber is prepared by the method for improving the drying and redispersion efficiency of nanocellulose according to any one of claims 1 to 6; the size range of the redispersed nanofibers is 2-40 nm in width, 100-3000 nm in length, and the redispermeability of the redispersion liquid is 50-95%.
8. An application of a nanofiber dispersion, characterized in that: Application of the redispersed nanofiber dispersion as claimed in claim 7 in the fields of composite materials, plastics, rubber, fracturing fluid or water reducing agent.
Citation Information
Patent Citations
Method for improving flocculation in drying process of micro / nano cellulose
CN114058027A
Redispersion method of dry solid of microfibrous cellulose and method of producing redispersion liquid of microfibrous cellulose
WO2020080119A1